TINGKAT PENGETAHUAN DAN KESIAPSIAGAAN MASYARAKAT MENGHADAPI BENCANA GEMPA BUMI DI KOTA PADANG PANJANG - Yola Afrida; dedi hermon; moh Nasir (DEPARTEMEN GEOGRAFI FIS UNP, 2017)
This research aims to, determine the level of public knowledge about the earthquake, knowing community preparedness against earthquake and determine the action to save themselves in situations and conditions. This type of research this is a descriptive quantitative. The subjects were community Padang Panjang as many as 134 people. Data collected by observation, tests, questionnaire and documentation. Samples of respondents in this study were drawn proportionally random sampling with the amount of 2% of the entire sample area. The research results as follows: 1) In the review of the level of public knowledge about disaster can be considered quite good. 2) For community preparedness against earthquake categorized poorly prepared. 3) For self-rescue measures on the circumstances considered less ready. After summation of the average percentage of each indicator obtained that knowledge and community preparedness are confronted by the earthquake based knowledge is still categorized as less ready with a percentage of 55.05%, so it is still necessary knowledge and preparedness are better for society to achieve the level of preparedness full in the face disaster later